Phytochemical characterization, anti-oxidant, anti-enzymatic and cytotoxic effects of Artemisia verlotiorum Lamotte extracts: a new source of bioactive agents - Suroowan, Shanoo; Llorent-Martínez, Eulogio Jose; Zengin, Gokhan; Dall’acqua, Stefano; Sut, Stefania; Buskaran, Kalaivani; Fakurazi, Sharida; Mahomoodally, Mohamad Fawzi (MDPI, 2022)
Artemisia verlotiorum Lamotte is recognized medicinally given its long-standing ethnopharmacological uses in different parts of the world. Nonetheless, the pharmacological properties of the leaves of the plant have been poorly studied by the scientific community. Hence, this study aimed to decipher the phytochemicals; quantify through HPLC-ESI-MS analysis the plant’s biosynthesis; and evaluate the antioxidant, anti-tyrosinase, amylase, glucosidase, cholinesterase, and cytotoxicity potential on normal (NIH 3T3) and human liver and human colon cancer (HepG2 and HT 29) cell lines of this plant species. The aqueous extract contained the highest content of phenolics and phenolic acid, methanol extracted the most flavonoid, and the most flavonol was extracted by ethyl acetate. The one-way ANOVA results demonstrated that all results obtained were statistically significant at p < 0.05. A total of 25 phytoconstituents were identified from the different extracts, with phenolic acids and flavonoids being the main metabolites. The highest antioxidant potential was recorded for the aqueous extract. The best anti-tyrosinase extract was the methanolic extract. The ethyl acetate extract of A. verlotiorum had the highest flavonol content and hence was most active against the cholinesterase enzymes. The ethyl acetate extract was the best α-glucosidase and α-amylase inhibitor. The samples of Artemisia verlotiorum Lamotte in both aqueous and methanolic extracts were found to be non-toxic after 48 h against NIH 3T3 cells. In HepG2 cells, the methanolic extract was nontoxic up to 125 µg/mL, and an IC50 value of 722.39 µg/mL was recorded. The IC50 value exhibited in methanolic extraction of A. verlotiorum was 792.91 µg/mL in HT29 cells. Methanolic extraction is capable of inducing cell cytotoxicity in human hepatocellular carcinoma without damaging normal cells. Hence, A. verlotiorum can be recommended for further evaluation of its phytochemical and medicinal properties.